Effects of partial replacement of sodium nitrite with Lactobacillus pentosus inoculation on quality of fermented sausages. Issue 5 (1st April 2019) - Zhu, Yinglian; Wang, Peng; Guo, Liping; Wang, Jun; Han, Rongwei; Sun, Jingxin; Yang, Qingli
Abstract: To improve quality and safety of fermented sausages, Lactobacillus pentosus isolated from kimchi was first used to partial replacement of sodium nitrite in sausages preparation. The study illustrated that the strain exhibited the ability of synthesis of nitrosylmyoglobin (Mb‐NO) due to the presence of nitric oxide synthase (NOS) and metmyoglobin (MetMb) reductase and possible generation mechanism of Mb‐NO was proposed. More importantly, the strain could prevent sausages from corruption due to its antibacterial ability. Furthermore, the strain could degrade nitrite and resist against lipid oxidation and protein decomposition. Texture and color of the sausages were superior to the controls. Hence, L. pentosus has great potential to partially substitute nitrite in sausages for its unique ability of producing NO‐Mb and antibacterial activity. The combination of L. pentosus and low levels of sodium nitrite addition would be a new significant strategy to improve the quality and safety of the fermented sausages. Practical applications: Results support the possibility of reducing sodium nitrite concentration in fermented sausages by inoculation with Lactobacillus pentosus in which provided superior color‐cured, microbial stability, and oxidation stability. The combination of L. pentosus and low levels of sodium nitrite addition can be applied by a simple process during processing which facilitates their use in meat industry.